2013
DOI: 10.1016/j.nlm.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

An Aplysia Egr homolog is rapidly and persistently regulated by long-term sensitization training

Abstract: The Egr family of transcription factors plays a key role in long-term plasticity and memory in a number of vertebrate species. Here we identify and characterize ApEgr (GenBank: KC608221), an Egr homolog in the marine mollusk Aplysia californica. ApEgr codes for a predicted 593-amino acid protein with the highly conserved trio of zinc-fingered domains in the C-terminus that characterizes the Egr family of transcription factors. Promoter analysis shows that the ApEgr protein selectively recognizes the GSG motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…This sample size is sufficiently powered (>= 0.80) only for very large effects (d > 1.4). However, this is similar to effect size we have previously observed in this paradigm for strongly regulated transcripts such as ApC/EBP, ApCREB1, and ApEgr (Bonnick et al, 2012; Cyriac et al, 2013). Moreover, we also conduct an integrated analysis of qPCR measures across both experiments, providing a sample size of at least 17 and adequate power for d >= 1.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This sample size is sufficiently powered (>= 0.80) only for very large effects (d > 1.4). However, this is similar to effect size we have previously observed in this paradigm for strongly regulated transcripts such as ApC/EBP, ApCREB1, and ApEgr (Bonnick et al, 2012; Cyriac et al, 2013). Moreover, we also conduct an integrated analysis of qPCR measures across both experiments, providing a sample size of at least 17 and adequate power for d >= 1.…”
Section: Methodssupporting
confidence: 91%
“…Previous research has shown that long-term sensitization training produces a rapid (within 1 hour) increase in the expression of six different transcripts in the pleural ganglia: ApC/EBP (GenBank: U00994; Alberini, Ghirardi, Metz, & Kandel, 1994), ApCREB1 (GenBank: NM_001256437; Bartsch, Casadio, Karl, Serodio, & Kandel, 1998), ApEgr (GenBank: KC608221; Cyriac et al, 2013), ApTBL-1 (GenBank: U57369; Liu et al, 1997), ApCalmodulin (GenBank: NM_001204580; Zwartjes et al, 1998), and an reductase-related protein (GenBank: NM_001204605; Zwartjes et al, 1998). To date, however, there have been no comprehensive efforts to characterize the rapid transcriptional response to long-term sensitization training (though see Castellucci, Kennedy, Kandel, & Goelet, 1988; Liu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The table below lists some well-known IEGs expressed in the nervous system. Most IEGs found in mammals are conserved across many species, from invertebrates such as C. elegans [53], Aplysia [54] and Drosophila [55] to vertebrates, but only a subset have been tested to see whether they are rapidly induced by neuronal activity.…”
Section: Figurementioning
confidence: 99%
“…We have previously analyzed the transcriptional correlates of LTS encoding (Herdegen et al 2014b), showing that 1 h after training there is a strong up-regulation of 81 transcripts, including those encoding transcription factors and transcription-factor regulators: ApC/EBP (GenBank: U00994; Alberini et al 1994), ApCREB1 (GenBank: NM_001256437; Bartsch et al 1998), ApEgr (GenBank: KC608221; Cyriac et al 2013), and ApC/EBPγ (GenBank: EB233406).…”
mentioning
confidence: 99%
“…These screens plus additional gene-of-interest studies have identified several changes at the level of mRNA expression that accompany the maintenance of LTS memory. Some changes persist from the encoding phase (Herdegen et al 2014a), including up-regulation of ApEgr (GenBank: KC608221; Cyriac et al 2013), ApGlyT2 (sodium-and chloride-dependent glycine-dependent transport 2, GenBank: XM_005092349), ApVPS36 (Vacuolar protein-sorting-associated protein 36-like) and an uncharacterized transcript (LOC101862095, GenBank: XM_005113453). Others emerge after encoding, including a delayed increase in the expression of ApBiP (GenBank: NM_001204652; Kuhl et al 1992), ApCalreticulin (GenBank: NM_001204594; Kennedy et al 1992), ApTBL-1 (GenBank: NM_001204563; Liu et al 1997), and Sensorin (GenBank: NM_001204654; Schacher et al 2000).…”
mentioning
confidence: 99%